South West Africa and the United Nations - Carroll, Faye (Book collections on Project MUSE., 1967)
In 1967, South West Africa -- which was controlled by the Republic of South Africa -- was the only remaining mandated territory from the old League of Nations that had not either gained its independence or come under trusteeship of the United Nations. The sparsely populated region became a center of international controversy and protest as it had come to be a symbol of colonialism and racism. In this study, Faye Carroll traces the twenty-year dispute between South Africa and the United Nations, carefully examining the legal, political, and moral issues involved. She also provides an introductio.